SUBMARINE VOLCANO CHARACTERISTICS IN SABANG WATERS - Hananto Kurnio; Subaktian Lubis; Hersenanto Catur Widi (BULLETIN OF THE MARINE GEOLOGY, 2015)
The aim of the study is to understand the characteristics of a volcano occurred in marine environment, as Weh Island where Sabang City located is still demonstrated its volcanic cone morphology either through satellite imagery or bathymetric map. Methods used were marine geology, marine geophysics and oceanography. Results show that surface volcanism (sea depth less than 50 m) take place as fumaroles, solfataras, hot ground, hot spring, hot mud pool and alteration in the vicinities of seafloor and coastal area vents. Seismic records also showed acoustic turbidity in the sea water column due to gas bubblings produced by seafloor fumaroles. Geochemical analyses show that seafloor samples in the vicinities of active and non-active fumarole vent are abundances with rare earth elements (REE). These were interpreted that the fumarole bring along REE through its gases and deposited on the surrounding seafloor surface. Co-existence between active fault of Sumatra and current volcanism produce hydrothermal mineralization in fault zone as observed in Serui and Pria Laot-middle of Weh Island which both are controlled by normal faults and graben.Keywords: submarine volcano, hydrothermal mineralization, Sabang-Weh-Aceh. Tujuan kajian adalah memahami karakteristik suatu gunungapi yang berada dalam lingkungan marin, sebagaimana Pulau Weh dimana Kota Sabang terletak masih menunjukkan morfologi kerucut volkaniknya baik melalui citra satelit maupun batimetri. Metoda yang digunakan adalah geologi kelautan, geofisika kelautan dan oseanografi. Hasil menunjukkan bahwa volkanisma permukaan (kedalaman laut kurang dari 50 m) terdapat dalam bentuk fumarola, solfatara, lahan panas, mata air panas, kolam lumpur panas dan alterasi sekitar lobang kepundan dasar laut dan pantai. Rekaman seismik juga menunjukkan turbiditas akustik dalam kolom air laut akibat gelembung gas yang dihasilkan oleh fumarola dasar laut. Analisis geokimia menunjukkan bahwa contoh-contoh dasar laut sekitar lobang kepundan fumarola yang aktif maupun tidak aktif kaya akan logam tanah jarang. Ini ditafsirkan bahwa proses fumarola tersebut membawa REE melalui gas-gasnya dan mengendapkannya pada permukaan dasar laut di sekitar. Ko-eksistensi antara Sesar Sumatera aktif dan volkanisma Resen menghasilkan mineralisasi hidrotermal dalam zona sesar seperti teramati di Serui dan Pria Laot - bagian tengah Pulau Weh yang keduanya dikontrol oleh sesar normal dan graben. Kata kunci: gunungapi bawah laut, mineralisasi hidrotermal, Sabang-Weh-Aceh.